Prevalence of syphilis and sexual behavior and practices among adolescents MSM and TrTGW in a Brazilian multi-center cohort for daily use of PrEP - Mateus Rodrigues Westin; Yuppiel Franmil Martinez; Ana Paula Silva; Marília Greco; Lucas Miranda Marques; Guilherme Barreto Campos; Matheus de Paula Alves; Alessandra Mancuzzo; Unaí Tupinambás; Dirceu Bartolomeu Greco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Syphilis has reemerged as a serious public health problem in Brazil and worldwide, disproportionately affecting men who have sex with men (MSM) and travestis and transgender women (TrTGW). Studies on sexually transmitted infections (STI) in adolescents from these key populations are relatively scarce. This is a Brazilian multi-center, cross study with prevalence analysis, using as baseline the PrEP1519 cohort of sexually active MSM and TrTGW adolescents, recruited from April 2019 to December 2020. Analyses were made using the dimensions of vulnerability to STI/HIV and logistic regression models were conducted to estimate the odds ratios of the association between the predictor variables and positive treponemal test for syphilis at the moment of entry in the study. In total, 677 participants were analyzed; participants' median age was 18.9 years (IQR: 18.1-19.5); 70.5% (477) self-declared as black; 70.5% (474), as homosexuals/gays; and 48 (7.1%), as trans women or travestis. The baseline prevalence of syphilis was 21.3%. In the final logistic regression model, higher chance of syphilis was associated with: self-reported episode of STI in the last 12 months (OR = 5.92; 95%CI: 3.74-9.37), sex worker (OR = 3.39; 95%CI: 1.32-8.78), and < 11 years of schooling (OR = 1.76; 95%CI: 1.13-2.74). The prevalence of syphilis among MSM/TrTGW adolescents aged from 15 to 19 years was alarming, much higher than the described for the general population within this age range and associated with vulnerability factors. This reinforces the urgent need to strengthen public health programs to debate about race, gender, sexuality, and prevention.